Efficacy and safety of small interfering RNA (siRNA) therapies for hypertriglyceridemia and mixed dyslipidemia: an updated systematic review and meta-analysis - Gao, Yifan; Bai, Yanmin; Mu, Xu; Pang, Xingxue (Frontiers in Pharmacology, 2026)
BackgroundHypertriglyceridemia (HTG) and mixed dyslipidemia are significant risk factors for cardiovascular diseases. Despite the widespread use of traditional therapies, many patients continue to experience elevated triglycerides and residual cardiovascular risk. Small interfering RNA (siRNA) therapies represent a novel approach to lipid-lowering treatment.MethodsA systematic review and meta-analysis were conducted on randomized controlled trials comparing siRNA versus placebo for hypertriglyceridemia or mixed dyslipidemia. The search included PubMed, Cochrane Library, Web of Science, and Embase databases from inception to 1 October 2025, limited to English-language publications. Data extraction was performed independently by two authors.ResultsEight RCTs involving 2,671 participants met the inclusion criteria. siRNA therapies significantly reduced triglycerides (TG) (MD, −52%; 95%, −57.9 to −46.2), non-high-density lipoprotein cholesterol (non-HDL-C) (MD, −21.9%; 95%, −26 to −17.7), very low-density lipoprotein cholesterol (VLDL-C) (MD, −49.5%; 95%, −60.1 to −38.9), apolipoprotein B (apoB) (MD, −12.6%; 95%, −16.4 to −8.8), and remnant cholesterol (MD, −64.8%; 95%, −81.7 to −47.9)compared with placebo. The reduction in TG was particularly notable. Subgroup analysis revealed that ANGPTL3-targeted therapies resulted in more substantial reductions in low-density lipoprotein cholesterol (MD, −13.2%; 95% CI, −20.1 to −6.2), while APOC3-targeted therapies had a neutral effect on LDL-C levels (MD, 0.6%; 95% CI, −5.7–6.9) (p for interaction = 0.00001). On the other hand, APOC3-targeted therapies significantly increased high-density lipoprotein cholesterol levels (MD, 40.9%; 95% CI, 31.6–50.2), whereas ANGPTL3-targeted therapies led to a reduction in HDL-C levels (MD, −20.2%; 95% CI, −25.4 to −14.9) (p for interaction = 0.00001). No significant differences were observed in the risk of adverse events between siRNA therapy and placebo (RR, 1.02; 95% CI, 0.96–1.09).ConclusionsiRNA therapies demonstrate significant efficacy in reducing triglycerides and improving lipid profiles in patients with HTG and mixed dyslipidemia. APOC3-targeted treatments primarily reduce triglycerides while increasing HDL-C, whereas ANGPTL3-targeted therapies offer broader lipid modulation, including substantial reductions in LDL-C. Both therapies demonstrate favorable safety profiles.